PENGARUH PRENATAL YOGA TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III DI PMB C DESA PASIRLAJA KECAMATAN SUKARAJA KABUPATEN BOGOR TAHUN 2023 - Aisyah, Yeki Supriaten (Politeknik Tiara Bunda, 2022)
The process of pregnancy will cause varios changes in all body systems, these changes have an impact on the cardiovascular system, respiratory system, hormonal system, gastrointestinal and musculoskeletak system. The effect of prenatal yoga on Sleep Quality in Third Trimester Pregnant Women. Result of research and discussions carried out in the independent practice of midwife NH for the period October - December with a total of 30 pregnant women. Basic maternal examinations carried out by midwives for grandchildren are the most important part of prenatal care during pregnancy. This examination aims to monitor the general health of pregnant women, the development of pregnancy, and the health of the fetus. The influence of prenatal yoga on the quality of sleep in pregnant women in the third trimester. It can be concluded that there is a positive and significant influence from implementing prenatal yoga on the quality of sleep of pregnant womwn in the third trimester. The majority of respondent showed an improvement in sleep quality after undergoing prenatal yoga, wich indicates that this activity helps in overcoming sleep problems in third trimester pregnant women.